Pelatihan Penulisan Jurnal Ilmiah untuk Civitas Akademika Universitas Brawijaya Malang - Ibnu Hajar; Martin Choirul Fatah; Edy Ispranyoto; Agus Yogiyanto; yuliansyah yuliansyah; Supriadi Legino (Sekolah Tinggi Teknik - PLN, 2020)
In high education, scientific journal has an important role in advancing the development of sciences as well as career development for researchers and academics. For the academics community (lecturer, researcher, and student), of course they have to do research. After research finished, and then it will be finished to do a research report. The research report has varying forms. For lecturer research it is usually in the form of a research report, while research report as an end product from every high education level, it can be a thesis, or dissertation. For widely publication of a result of research, a research report can be made in a article that it can be published in reputable scientific journal both nasionally and internationally. But generally, most academics community do not / have not thought about doing research and then the results of their research are written and published in the form of a journal. It is right that several difficulties that faced akademics community in writing a scientific journal such as lazy, don’t know (there is no idea) about what will be written, there is a idea but don’t know how to start it, and various other reason. Therefore, various obstacles, and difficulties they faced in writing a scientific journal, the team of community services (PKM) of Electrical Engineering, STT PLN Jakarta offer a solution i.e workshop in writing scientific journal through community service activities. This workshop has been carried out due to cooperation with our partner that is Machanical Engineering Department, Engineering Faculity, Brawijaya University. Our partner Brawijaya University prepared participants and workshop venue. The implementation of this workshop in writing scientific journal received a very good response from the participants and provide motivation to them to do research which is then published in the form of scientific journal articles.